Pharmacognostic Standards for Uvaria chamae P. Beauv. Leaves (Annonaceae) (Nigerian Journal of Pharmaceutical Research, 2023)
BackgroundStandardisation as a tool in quality control ensures purity, safety and efficacy of herbal medicines. Uvaria chamae from the family Annonaceae has wide medicinal application which includes its use as a febrifuge and as an anti-inflammatory.Objective: The study was aimed at developing some Pharmacognostic standards for the leaves of U. chamae.Material and Methods: Uvaria chamae plant was collected, identified and authenticated. Fresh leaves were examined macroscopically and microscopically based on standard procedures. Fluorescence behavior was assessed by adding various reagents and viewing at daylight, 254 nm and 365 nm. Chemomicroscopy and physicochemical analysis of powdered samples were done using standard procedures. Phytochemical and Thin layer chromatographic analysis of the extracts were also carried out.Results: Leaves of U. chamae are alternately arranged and elliptic in shape. The abaxial surface has straight polygonal epidermal cells with paracytic stomata. Vascular bundles are arranged in fan shape from the transverse section of the leaf. Chemomicroscopic evaluation revealed the presence of lignin, starch and oil. Alcohol and water soluble extractive values were 4.00 ± 0.00 and 5.6 ± 0.67, respectively. The membrane stabilization activity of the extracts at 0-1 mg exceeded that of the standard drug diclofenac. The ethyl acetate fraction had the highest percentage of inhibition of haemolysis at 0.4 mg.Conclusion: The features established in this study may contribute in the identification and quality control of U. chamae.